Nahdlatul Ulama (NU) dan Kontribusinya dalam Memperjuangkan Kemerdekaan dan Mempertahankan Negara Kesatuan Republik Indonesia (NKRI) - Amin Farih (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2016)
Religious mission of Nahdlatul Ulama (NU) in consolidating power against Dutch colonialism is a part of the struggle of NU for defending religious ideology and nationalism, as a form of patriotism (ḥubbu al-waṭan). NU had to expel the Dutch colonialists because it is religious teaching. The law had already become a decision of the religious leaders (kyai) of NU, which ultimately rise